2015
DOI: 10.1021/acs.energyfuels.5b00768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt on the Crystal Growth and Adhesion Force of Clathrate Hydrates

Abstract: In the offshore oil and gas developments, the problems in relation to hydrate flow assurance are always influenced by the existence of salt in the pipeline systems. Even though the salt effects are essential factors associated with the adhesion force between clathrate hydrate and aqueous solutions, the roles of salt in hydrate adhesion behaviors have rarely been considered. This study aims at understanding the effects of salt on not only the adhesion force variations but also the transformation of hydrate grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…We found that our estimates for the work of adhesion are consistent with experimental measurements [93], suggesting that simulations such as those presented here could be useful for the estimation of adhesion force interactions between hydrate particles and water droplets. To our knowledge, this is the first determination of the hydrate-water adhesive forces achieved by employing molecular simulations under realistic conditions, as most previous experimental studies were performed using hydrates stable at atmospheric pressure, such as cyclopentane [93,[95][96][97]. Our work contributes to closing the gap between experimental and realistic models of clathrate hydrates.…”
Section: Discussionmentioning
confidence: 87%
“…We found that our estimates for the work of adhesion are consistent with experimental measurements [93], suggesting that simulations such as those presented here could be useful for the estimation of adhesion force interactions between hydrate particles and water droplets. To our knowledge, this is the first determination of the hydrate-water adhesive forces achieved by employing molecular simulations under realistic conditions, as most previous experimental studies were performed using hydrates stable at atmospheric pressure, such as cyclopentane [93,[95][96][97]. Our work contributes to closing the gap between experimental and realistic models of clathrate hydrates.…”
Section: Discussionmentioning
confidence: 87%
“…(6) Step 5 was repeated until the colorless solvent dripped through the filter paper, meanwhile the filter needed to be replaced after a few rounds for better results. (7) The precipitates were dissolved into toluene with a mass ratio of 1:20 after collecting from the filter paper. (8) To remove solid particles, the mixture was shaken for 20 min and divided equally into Teflon tubes before centrifuging at 20,000g for 20 min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…1,5,6 However, thermodynamic inhibitors are economically and environmentally unacceptable. 1,7 Another strategy proposed to reduce the plugging tendency of conventional production systems is the addition of kinetic inhibitors.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the above results clearly illustrated that hydrate adhesion strength on surfaces at the microscale were affected by the surfaces' chemical properties in general. 184 The above-mentioned studies carried out by Das et al supported such a conclusion. 163 Although the OTS-coated surface had higher surface energy than the FS-coated surface, the hydrate adhesion force on the OTS-coated surface was lower.…”
Section: Anti-hydrate Adhesion Surfacesmentioning
confidence: 80%